Interest Rate Volatility, Monetary Policy and Financial Sector in Developing Countries - Umoru, David; IMIMOLE, Fabius Oshiotse (Acta Universitatis Danubius. Œconomica, 2023)
The study investigated the effects of interest rate volatility and changes in money supply policy on the financial sector of selected African countries. The dynamic panel model and GARCH model were used for estimation. A secondary data collection instrument was used. A sample of ten countries in the African Union was used for analysis. In terms of policy findings, the results revealed that interest volatility and money supply were stationary, and co-integrated with long-run equilibrium relationships among African Union member countries within the study periods. Interest rate volatility negatively impacted the financial sector stability in African Union countries. A percentage increase in the volatility in interest rate accounted for 0.19 percent instability in the financial system of the African Union economies while a similar proportion of variation in money growth stabilized the financial sector by 0.18 percent. Negative spikes or trends of interest rate variability in the financial sector were found for all the African Union member states considered in this study. Specifically, the financial sectors of developing nations are at risk in the presence of volatility in the interest rate. With the fixed effect model, financial sector stability had its impact at lag 1 and it was extensively significant. The originality of the research derives from the fact that the methodologies of the dynamic panel model and GARCH model were deployed in evaluating the effects of variations in interest rate and money growth on the financial sectors of African countries. Interest rate volatility had a Granger causality effect on the financial sector stability of African Union member states in the short run. The study accordingly recommends the need for the governments of the countries covered by the study to intensify efforts to enhance robust financial sector stability by implementing a friendly interest rate policy. Policymakers of the African Union should be guided by the sensitivity of the financial sector of the AU economies to variations in interest rates. Taken together, a stable monetary system is a considerable tool for sustaining the stability of the financial system.